Price transmission in the pangasius value chain from Vietnam to Germany - Ankamah-Yeboah, I.; Thong, N.T.; Bronnmann, J.; Nielsen, M.; Roth, E.; Schulze-Ehlers, B. (Aquaculture Reports, 2019)
Evidence of market integration between farmed pangasius and wild-caught whitefish is provided in the literature, pointing towards pangasius prices being determined on the large international whitefish market. In the presence of price transmission in the value chain, global growth of pangasius farming does therefore not in itself reduce the farm-gate prices in Vietnam. In this paper, price transmission in the pangasius value chain from farmers in Vietnam, via export to final consumption in Germany, is tested using the Johansen cointegration framework. Price transmission is identified both between farm-gate prices and export prices in Vietnam and between export prices and retail prices in Germany. The Law of One Price was rejected in both cases, indicating imperfect price transmission. Weak exogeneity tests of market leadership identify a value chain with downstream market leadership consisting of German retailers leading exporters, which themselves lead farmers. The implication is that growth of Vietnamese pangasius farming can continue, ceteris paribus, without reducing prices substantially. Vietnamese farmers can invest in expansions without fearing self-inflicted price falls, but farmers and local communities remain prone to fluctuations following from supply and demand changes at the international whitefish market outside of their control.
Research Article
Keywords: Price transmission; Cointegration; Law of one price; Weak exogeneity; Global value chains; Pangasius